A multicountry, multisector general equilibrium model system with endogenous trade - David P. Vincent (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
Our aim in this paper is to describe the theory of a multicountry multisector general equilibrium model system whose specification preserves as far as is possible; (i) the considerable amount of 10 detail, (ii) the numerous prospects for relative price induced substitution and (iii) the operational flexibility, now found in the most advanced of the single country models. To do this, we take as our reference point the Australian ORANI model (Dixon et al (1982)) which is the most comprehensive (in terms of its treatment of within country 10 linkages and substitution prospects) and flexible (in terms of its ease of application to a range of policy shocks) of the single country models developed to date. Starting with a somewhat simplified version of the ORANI system (which describes intersectoral linkages within one economy and commodity trade flows - exports from it to the rest of the world and imports from the rest of the world to the demand categories in which they are used -) we extend it to a c+1 block system describing intersectoral linkages between the c countries into intermediate input and final demand categories of each country and trade flows from each of the countries to the c+1 block (which depicts.an aggregation of all remaining countries). Such a framework would.be suitable for studying effects of internal (originating in any of the c countries) and external (to the group of c countries) shocks on macroeconomic and sectoral variables in each country and on trade flows between countries. Given its considerable attention to regionalised (country to country) flows at the 10 level the system is especially applicable to a group of c countries between which the degree of economic integration is high. The most obvious example is the 10 member customs union of the EEC. Other examples include the five member countries of ASEAN, the developed countries (USA, Japan, Australia) of the so-called Pacific rim and the trans-Tasman economic integration between Australia and New Zealand.
Keywords: 330